O potrzebie nauczania interpunkcji we współczesnej szkole - Krzyżyk, Danuta; Synowiec, Helena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Nasz szkic dedykujemy pamięci Profesora Henryka Kurczaba, który w swojej twórczości naukowej i działalności dydaktycznej wiele miejsca poświęcał kulturze języka w szkole oraz problemom integrowania celów i treści kształcenia. Upominamy się o docenienie interpunkcji w szkolnym kształceniu językowym. Zwracamy uwagę na słabą znajomość przez uczniów reguł interpunkcyjnych i niestosowanie tych reguł w tekstach pisanych. Świadczą o tym liczne błędy w przestankowaniu i związane z nimi błędy składniowe. Wskazujemy na cywilizacyjne, kulturowe i dydaktyczne czynniki, które mają wpływ na obniżanie się poziomu sprawności interpunkcyjnej dzieci i młodzieży. Na podstawie badań sondażowych omawiamy stan przygotowania metodycznego polonistów do nauczania interpunkcji, m.in. znajomość przez nich słowników i poradników interpunkcyjnych, rodzajów ćwiczeń, a także uwzględnianie zasady integrowania interpunkcji z nauczaniem składni. W aneksie szkicu zamieszczamy – istotną dla podniesienia świadomości dydaktycznej nauczycieli – klasyfikację błędów interpunkcyjnych. Została ona opracowana przez profesora Jerzego Podrackiego – językoznawcę i dydaktyka języka.

Our essay is dedicated to the memory of Professor Henryk Kurczab, who in his scientific output and teaching activities devoted a lot of time to the language culture at school and issues concerning integrating the purposes and contents of education. We demand appreciation for the punctuation in school linguistic education. We draw attention to pupils’ poor knowledge of punctuation rules in written texts. It is proved by numerous mistakes in interpunction and related syntax errors. We point to civilization and culture as well as didactic factors, which influence the decrease of the punctuation skills levels of children and youth. On the grounds of survey research we are discussing the condition of Polish teachers’ methodological preparation to teach punctuation, among others their familiarity with dictionaries and punctuation guides, types of exercises and the application of the principle of integrating the punctuation with teaching syntax. The attachment to this essay includes the classification of punctuation errors, which is important to increase the teachers’ didactic awareness. It was prepared by professor Jerzy Podracki – a linguist and language didactician.
On the need to teaching punctuation in a modern school
Keywords: interpunkcja; błędy interpunkcyjne; typologia błędów interpunkcyjnych; nauczanie interpunkcji; integracja interpunkcji ze składnią; punctuation; punctuation errors; typology of punctuation errors; teaching punctuation; integration of punctuation and syntax.